2017
DOI: 10.1186/s12872-017-0624-0
|View full text |Cite
|
Sign up to set email alerts
|

Does infection with human immunodeficiency virus have any impact on the cardiovascular outcomes following percutaneous coronary intervention?: a systematic review and meta-analysis

Abstract: BackgroundA direct link between human immunodeficiency virus (HIV)-infected patients and the risk of cardiovascular diseases (CVD) has been shown in recent scientific research. However, this issue is controversial since other previous reports showed no apparent impact of HIV or its anti-retroviral drugs on the cardiovascular system. We aimed to systematically compare the postinterventional adverse cardiovascular outcomes which were observed in patients with and without HIV infection during a mean follow up per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…As for patients with coronary artery disease, the indication between percutaneous coronary intervention (PCI) or CABG is based on patient's conditions, comorbidities and coronary anatomy. For CABG and PCI, HIV-positive patients exerted similar results to those observed in the general population (Badr et al, 2015;Bundhun et al, 2017;Moran et al, 2020). HIV-status is known to be accompanied by a pro-inflammatory status with increased platelet reactivity (Hauguel-Moreau et al, 2017;Rethy et al, 2020), but this does not seem to directly translate into clinically observable adverse events.…”
Section: Surgical Myocardial Revascularizationmentioning
confidence: 60%
See 1 more Smart Citation
“…As for patients with coronary artery disease, the indication between percutaneous coronary intervention (PCI) or CABG is based on patient's conditions, comorbidities and coronary anatomy. For CABG and PCI, HIV-positive patients exerted similar results to those observed in the general population (Badr et al, 2015;Bundhun et al, 2017;Moran et al, 2020). HIV-status is known to be accompanied by a pro-inflammatory status with increased platelet reactivity (Hauguel-Moreau et al, 2017;Rethy et al, 2020), but this does not seem to directly translate into clinically observable adverse events.…”
Section: Surgical Myocardial Revascularizationmentioning
confidence: 60%
“…HIV-status is known to be accompanied by a pro-inflammatory status with increased platelet reactivity (Hauguel-Moreau et al, 2017;Rethy et al, 2020), but this does not seem to directly translate into clinically observable adverse events. A recent metanalysis of 821 HIV-positive and 1147 HIV-negative patients undergoing PCI demonstrated that HIVpositive patients have similar mortality (odds ratio 1.16, 95% confidence interval 0.50-2.68, P = 0.74), no significant increase in recurrent myocardial infarction (odds ratio 1.32, 95% confidence interval 0.88-2.12, P = 0.17), target vessel revascularization (odds ratio 1.22, 95% confidence interval 0.72-2.06, P = 0.46) or major adverse events (odds ratio 1.47, 95% confidence interval 0.44-4.89,P = 0.53) (Bundhun et al, 2017). Those results seem to corroborate the outcomes observed in the CABG scenario.…”
Section: Surgical Myocardial Revascularizationmentioning
confidence: 95%
“…Fifteen studies that met the quality appraisal are included in the systematic review, as discussed in Table 1 [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…En este grupo, las tasas de trombosis del stent fueron superiores en aquellos con recuento CD4 < 200 cl/mm3 (HR 5.9; IC95% 1,4-2,5; p 0.016) y la ausencia de terapia antirretroviral fue un predictor independiente de muerte cardiovascular (HR 9.9; IC95% 2.1-46; p 0.03). En 2017, un metaanálisis de Bundhun et al 27 incluyó cerca de 2.268 pacientes (821 sero-positivos vs 1447 sero-negativos) sometidos a angioplastía coronaria. No hubo diferencias significativas en términos de mortalidad global, mortalidad cardíaca, Infarto al miocardio recurrente, accidente cerebrovascular isquémico o eventos cardiovasculares mayores al comparar ambos grupos en un seguimiento hasta 3 años.…”
Section: Revascularización Miocárdica En El Paciente Portador Del Virusunclassified